Association of eating habits with mitochondrial DNA copy number in eveningness chronotypes: origin research - Ali, Shazia; Maqsood, Madeeha; Ahmed, Suhaib; Feroz, Shagufta (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the relationship between eating habits and mitochondrial deoxyribonucleic acid copy number in adult cases of eveningness chronotypes. Method: The cross-sectional, analytical study was conducted from September 2022 to June 2023 at the Physiology Department of the Islamic International Medical College, Rawalpindi, in collaboration with the Genetic Resource Centre, Rawalpindi, Pakistan, and comprised adult subjects who were assessed using the Morningness-Eveningness Questionnaire. The participants’ eating habits were assessed using the Healthy Eating Assessment Questionnaire, and on they were divided into those with healthy eating habits in group A and those with unhealthy eating habits in group B. Deoxyribonucleic acid was extracted using the Chelex method, the mitochondrial deoxyribonucleic acid copy number of all participants was quantified using quantitative polymerase chain reaction. Data was analysed using SPSS 27. Results: Of the 80 subjects, 30(37.5%) were males and 50(62.5%) were females. The overall mean age was 24.27±6.91 years (range: 18-45 years). There were 40(50%) subjects in each group. The mean mitochondrial deoxyribonucleic acid copy number in group A was 2.74±0.14 compared to 2.26±0.25 in group B (p<0.001). Conclusion: Subjects with healthy eating habits exhibited higher mitochondrial deoxyribonucleic acid copy numbers, indicating reduced damage to mitochondrial deoxyribonucleic acid. Key Words: Mitochondria, Mitochondrial DNA, Eating habits, Chronotype.